PENYIDIKAN TINDAK PIDANA PERJUDIAN DALAM GELANGGANG PERMAINAN OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Putri, Hana Aulia; ', Erdianto; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The social problem that is still mushrooming in the community is the phenomenon of gambling. Gambling is an act that is contrary to religious, moral, moral and legal norms, and is harmful to the livelihoods and lives of the people, nation and state. People who use the opportunity to play gambling as stipulated in article 303 of the Criminal Code are subject to criminal sanctions as stipulated in article 303 bis of the Criminal Code, with a maximum imprisonment of four years or a maximum fine of Rp.10,000,000.00 (ten million rupiah). In Pekanbaru City, gambling cases are increasingly happening with various modes used, one of which is gambling in the game arena with a mode as a children's playground. Game venues that should be played by children but misused or converted as gambling places played by adults. The purpose of this thesis writing is to find out the investigation of the crime of gambling in the game arena by the Pekanbaru City Police to find out the obstacles in investigating the crime of gambling in the game arena by the Pekanbaru City Police, and to find out the efforts made by the Resort police Pekanbaru City in overcoming barriers to investigating gambling crimes in the game arena.This type of research can be classified in the type of empirical juridical research. Because in this study the author directly conducts research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru City Police Department. The results of research conducted by the author are first, Investigation of criminal acts of gambling in the playground by Pekanbaru City Police Force is carried out with the stages of receiving reports / complaints, investigations, stages of investigation and forced efforts. Second, the obstacles faced in conducting investigations are the difficulty of proof because the place of the game is closed, lack of awareness and legal awareness of the community, and the intervention of the parties or certain elements. Conducted by Pekanbaru City Police in overcoming barriers is holding special learning activities for the police, conducting legal counseling, conducting patrols and routine surveillance, fighting police officers who protect crime, and forming a special team to spy on places that are often used as gambling places.Keywords: investigation - gambling - game arena